An experimental work on the performance of new integration of photovoltaic panel with solar still in semi-arid climate conditions. (February 2020) - Abd Elbar, Ayman Refat; Hassan, Hamdy
Abstract: This paper presents an experimental work on the performance of new coupling of photovoltaic (PV) panel with single slope solar still. The coupling is based on integrating the PV over the still condenser where the PV output power is transmitted directly to the saline water through an electrical resistance embedded inside the still basin. This integration enables the PV to transmit its reflected solar energy to the saline water. The performance of this system (PV + solar still) is studied for black steel wool fibers (BSWF) in the basin and for natural and forced convection air cooling (FAC) of the PV and still condenser. The results indicate that integrating the PV with the conventional solar still (CSS) and with the CSS plus the BSWF increases the still productivity by 9%, and 23%, respectively. Moreover, the highest desalinated yield and maximum still efficiency are achieved in case of CSS + PV + BSWF + FAC however, the CSS has the lowest yield and efficiency. Using PV as a reflector rises still productivity by 3.2% and achieves the minimum cost compared to other systems. Using PV + BSWF + FAC with CSS has approximately the same freshwater cost as CSS, but it raises its daily yield and efficiency by 30% and 35%, respectively. Highlighted: Conventional still with photovoltaic, steel fibers and forced cooling has the highest yield. Using photovoltaic and steel fibers with conventional still increases its productivity by 23%. Conventional solar still has the lowest still efficiency compared to other modified stills. Conventional still with photovoltaic, steel fibers and forced cooling has maximum efficiency. Still with photovoltaic as a reflector has the minimum cost per liter.